A Comprehensive Program to Reduce Tobacco-related Cancers Through Actions by a National Cancer Institute-designated Cancer Center. (3rd November 2022) - Cofer, Jennifer; Hurst, Alex N.; Winter, Tiffany; Moreno, Mark; Cinciripini, Paul M.; Walsh, Michael T; Tektiridis, Jennifer; Hawk, Ernest
Tobacco use accounts for 30% of all cancer-related deaths worldwide and 20% in the US, despite effective, evidence-based interventions for reducing tobacco use and tobacco-related cancers and deaths. In 2012, to reduce the burden of tobacco-related cancer and associated population-level risks across Texas, The University of Texas MD Anderson Cancer Center initiated the EndTobacco ® program to promote statewide cancer control activities. We created evidence-based initiatives, established selection criteria, and implemented actions involving policy, education, and tobacco treatment services. As a result, EndTobacco has supported, educated, and convened local and state coalitions in policymaking; provided tobacco treatment education to health professionals; implemented Texas' only certified tobacco treatment training program; and led an initiative to enhance the tobacco-free culture of the state's publicly funded university system. Supported by commitments from MD Anderson, we developed and implemented evidence-based actions for tobacco control tailored to the center's mission, values, expertise, resources, and partnerships. By 2021, the adult smoking rate in Texas dropped from 19.2% (2014) to 13.2%. Contributors to this drop include state tobacco control policies, programs and services from multiple agencies and associations, and EndTobacco activities that complement the statewide effort to prevent youth smoking initiation and increase quit attempts among youth and adults.